Journal of Human Sport and Exercise - 2018 - Spring Conferences of Sports Science 2018
DOI: 10.14198/jhse.2018.13.proc2.28
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 12-week-long program of vigorous-intensity physical activity on the body composition of 6-and 7-year-old children

Abstract: The purpose was to study the effects of a program of vigorous-intensity physical activity (PA) on the body composition of children. This investigation involved 32 school children from 6 to 7 years old (14 males 6.57 ± 0.51 yr., and 18 females 6.33 ± 0.49 yr.). The variables measured were: body weight, fat-free mass (FFM), fat mass (FM), total body water (TBW), basal metabolic rate (BMR), body mass index (BMI), fat-free mass index (FFMI) and fat mass index (FMI). The body composition analysis was performed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Among the benefits provided by positive habits figures a decrease in the risk of suffering from diseases such as osteoporosis, cancer or obesity (Warburton and Bredin, 2017). PA produces an improvement in insulin sensitivity, develops cardiorespiratory fitness through adaptations in the cardiovascular system and helps decrease the percentage of fat mass (Fransson et al, 2018; López-Sánchez et al, 2018). In addition, PA also generates a multitude of benefits at a cognitive level, which are the focus of this research work.…”
Section: Introductionmentioning
confidence: 99%
“…Among the benefits provided by positive habits figures a decrease in the risk of suffering from diseases such as osteoporosis, cancer or obesity (Warburton and Bredin, 2017). PA produces an improvement in insulin sensitivity, develops cardiorespiratory fitness through adaptations in the cardiovascular system and helps decrease the percentage of fat mass (Fransson et al, 2018; López-Sánchez et al, 2018). In addition, PA also generates a multitude of benefits at a cognitive level, which are the focus of this research work.…”
Section: Introductionmentioning
confidence: 99%
“… 23 The intensity of physical activities in adolescents is an important factor for physiological responses, since it was observed that 15 min of vigorous intensity physical activity for three days per week in a 12 week intervention was already able to improve the cardiovascular health of 12–15-year old adolescents. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Activities with an aerobic predominance have been indicated to ight negative efects of anxiety and slight depressive states (Mc Donald, & Hodgdon, 1991); needing a minimal level or medium grade of activity to achieve a favourable inluence on the symptoms (Annesi, 2000). It has been concluded that physical exercise produces beneicial efects on people's health (Lubans, Foster, & Biddle, 2008;López et al, 2017López et al, , 2018, improving the sensation of wellbeing and mood (Ekkekakis, & Acevedo, 2006).…”
Section: Introductionmentioning
confidence: 99%